Applying an equity lens to pharmacogenetic research and translation to under‐represented populations. Issue 6 (30th July 2021) - Luczak, Tiana; Stenehjem, David; Brown, Jacob
Abstract: Since the publication of the Human Genome Project, genetic information has been used as an accepted, evidence‐based biomarker to optimize patient care through the delivery of precision health. Pharmacogenetics (PGx) uses information about genes that encode proteins involved in pharmacokinetics, pharmacodynamics, and hypersensitivity reactions to guide clinical decision making to optimize medication therapy selection. Clinical PGx implementation is growing from the dramatic increase in PGx studies over the last decade. However, an overwhelming lack of genetic diversity in current PGx studies is evident. This lack of diverse representation in PGx studies will impede equitable clinical implementation through potentially inappropriate application of gene‐based dosing algorithms, whereas representing a missed opportunity for identification of population specific single nucleotide variants and alleles. In this review, we discuss the challenges of studying PGx in under‐represented populations, highlight two successful PGx studies conducted in non‐European populations, and propose a path forward through community‐based participatory research for equitable PGx research and clinical translation.